Role of Innate Immune and Inflammatory Responses in the Development of Secondary Diabetic Complications - Plowman, Trevor J.; Shah, Mujtaba H.; Fernandez, Emely; Christensen, Hannah; Aiges, Myia; Ramana, Kota V. (Current Molecular Medicine, 2023)
Increased hyperglycemia due to uncontrolled diabetes is the major cause of secondary diabetic complications such as retinopathy, neuropathy, nephropathy, and cardiovascular diseases. Although it is well known that increased oxidative stress, activation of the polyol pathway, protein kinase C and increased generation of advanced glycation end products could contribute to the development of diabetic complications, recent studies implicated the role of innate immunity and its related inflammatory responses in the pathophysiology of secondary diabetic complications. Increased activation of oxidative stress signaling could regulate NLRP3 inflammasome-mediated innate immune responses as well as NF-ΚB signalosome-mediated pro-inflammatory responses. This review article focused on the pathogenic role of innate immune and inflammatory responses in the progression of hyperglycemia-induced secondary diabetic complications. Specifically, we discussed in depth how deregulated innate immune and inflammatory responses could lead to an aggravated release of cytokines, chemokines, and growth factors resulting in the development of various secondary complications of diabetes.
Keywords: Diabetes